2018
DOI: 10.1016/j.surg.2018.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for 30-day readmission after adrenalectomy

Abstract: Encouraging the appropriate use of laparoscopic adrenalectomy, preventing venous thrombotic events and surgical infections, and improving early post-operative follow-up in high-risk patients may decrease readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Readmissions represent a significant burden to the health care system (9). High readmission rates correlate with decreased quality of care, decreased patient well-being, and increased hospital costs (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Readmissions represent a significant burden to the health care system (9). High readmission rates correlate with decreased quality of care, decreased patient well-being, and increased hospital costs (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…RLA has been widely used in clinical practice, but it is prone to wound infection, bleeding, and even shock during postoperative care [22]. Dressings are considered to be an important method to promote wound healing and prevent bacterial infections [23].…”
Section: Discussionmentioning
confidence: 99%
“…This rate is between 5% and 15% after abdominal surgery 41 . Beck et al reported the readmission risk factors after adrenalectomy as high ASA score, diabetes, advanced age, primary adrenal cancer surgery, long operation time, operation type and postoperative complications 47 . In our series, readmission was 9.1% in the open approach and 3.4% in the laparoscopic approach and this was not statistically significant(p=0.297,p<0.05).Reasons for readmission were hypotension and pleural effusion in the open surgical approach group, and pancreatic fistula and wound infection in the area where the specimen was removed in the laparoscopic approach group.The limitations of our study were its' retrospective nature, limited number of patients and being conducted in a single center.…”
Section: Discussionmentioning
confidence: 99%